Physicochemical and Sensory Properties of Protein Isolate from Anchovy (Stolephorus insularis) - Meda Canti; Katarina Aninda Karisma Palupi; Maggy Thenawidjaja Suhartono (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2022)
Anchovy is one of the primary fishery commodities in Indonesia; however its development as fishery products is currently suboptimal. Due to its high protein content, anchovy is potential to be developed as a source of value-added fish protein isolate. This study aims to produce anchovy protein isolate (API) and evaluate its physical, chemical, and sensory properties. The API was prepared from defatted anchovy flour. Isolation of anchovy protein was carried out using a pH-shifting method. The API was then analyzed for its physicochemical (bulk density, color, proximate) and sensory properties. The results showed that anchovy protein  was more soluble at pH 11 and less at pH 5. Yield and protein recovery of API were 26.39 and 36.86% wb, respectively. The API had 92.20% protein, 3.64% moisture, 2.18% ash, 2.26% lipid, and 3.36% carbohydrate content on a dry basis. The results showed that the API exhibited good physical and sensory properties such as bulk density, color, the best score on sweetness, seaweed, bitterness, off-flavor, aroma, and rancid taste. There was no significant difference in sweet taste, off-flavor, aroma, and rancid taste between API and soy protein isolate (SPI) (p0.05). Overall, API demonstrated  satisfactory nutritional properties and potential use as food ingredients.